The Influence of Organizational Support with the Role of Work-Life Balance and Employee Involvement on Performance in Fire Service Officers - Rahmanda, Hadi; Yasri, Yasri (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines the influence of organizational support with the role of work-life balance and employee engagement on performance among fire department personnel in Padang City and Pariaman City. The research utilizes a quantitative approach with a causal research design, involving 290 respondents selected through purposive sampling technique. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4.0 software. The results indicate that work-life balance has a significant positive effect on performance (?=0.661, p<0.001), and employee engagement has a significant positive effect on performance (?=0.041, p=0.006). Organizational support significantly influences work-life balance (?=0.514, p<0.001) and employee engagement (?=0.686, p<0.001). However, the direct effect of organizational support on performance shows a minimal coefficient (?=0.000, p=0.010). The indirect effects reveal that work-life balance mediates the relationship between organizational support and performance (?=0.340, p<0.001), and employee engagement also mediates this relationship (?=0.368, p=0.010). These findings suggest that organizational support does not directly improve performance but works through enhancing work-life balance and employee engagement. The study contributes to human resource management literature by demonstrating the importance of dual mediation mechanisms in high-risk occupational contexts.